Índice de caminhabilidade no entorno de terminais de integração do transporte público coletivo na cidade de Aracaju - Possera, Danilo Santos (2021)
In recent years, there has been a notorious trend towards increasing the number of urban roads for motor vehicles, which has led to negligence in the creation of pedestrian routes. In relation to Aracaju, public transport is done exclusively through the bus system, thus, the collective public transport integration terminal (CPTIT), is characterized as a key point for local public transport and contributes to the concentration of pedestrians who start or finish their daily journeys, often around these CPTIT, through the walk. In this sense, the general objective of this research was to generate a walkability index around three CPTIT in the city of Aracaju. As for the research method adopted, it was descriptive, of a qualitative-quantitative nature. The study areas were divided into three regions, and the surroundings within a 500m radius of the CPTIT in the municipality of Aracaju were analyzed: Region 1 - surroundings of the CPTIT Minervino Fontes, located in the South Zone; Region 2 - around the CPTIT Governador Luiz Garcia, located in the Center Zone of Aracaju and Region 3 - around the CPTIT Maracaju, located in the North Zone. To determine the Aracaju walkability index, the method proposed by ITDP was used, in its entirety, through the iCam 2.0 tool. As results, it was observed for the surroundings of the CPTIT Minervino Fontes - Zona Sul, as for the categories, that two presented insufficient values: mobility (1.96) and environment (1.88). Values were inadequate for the other four categories: sidewalk (0.87); attraction (0.73); road safety (0.76) and public safety (0.65). The overall value of iCam for the surroundings of CPTIT Minervino Fontes was 1.14, considered insufficient. As for the area surrounding the CPTIT Governador Luiz Garcia - Zona Centro, it was observed that as for the categories, two presented sufficient value: mobility (2.19) and environment (2.14). Three categories had insufficient values, they are: sidewalk (1.22), attraction (1.44) and public safety (1.09). The value was inadequate for the road safety category (0.86). The general value of iCam for the surroundings of CPTIT Governador Luiz Garcia was 1.49, considered insufficient. The last environment evaluated was from the CPTIT Maracaju - North Zone, in which it was observed, as for the categories, that only the environment category (2.02) presented sufficient value. Two categories had insufficient values, they are: mobility (1.84) and attraction (1.12). The values were inadequate for the other three categories: sidewalk (0.93), road safety (0.57) and public safety (0.60). Finally, the overall value of the iCam was 1.18, considered insufficient for the CPTIT Maracaju. Thus, it is concluded that this research used efficient methodological and data collection procedures that were able to include the assessment of the walkability index in the city of Aracaju, which allow the understanding of the effect of sidewalk quality in the urban modality, in addition to identifying the main deficiencies in the infrastructure developed for pedestrians and, therefore, serves as an instrument to guide future projects or public and private policies that aim to improve walking in the city of Aracaju.